Factors Influencing Financial Report Quality and Accountability in Mosque Management - Chrisna, Heriyati; Andriany Nasution, Nina; Sasmita, Puteri Keshya Adisty (Institut Bisnis dan Informatika Kesatuan, 2025)
Mosque financial accountability is crucial for maintaining public trust, yet many mosques in Medan City face challenges in producing high-quality financial reports. This study aims to examine factors influencing the quality of mosque financial reports, including human resource competence, financial management practices, internal control systems, information technology utilization, stakeholder roles, and trustworthiness. Guided by Stewardship Theory, which emphasizes ethical management, the study explores how these factors enhance transparency in mosque financial reporting. A quantitative approach was used, with primary data collected through questionnaires from 21 mosque administrators in Medan City, selected via non-probability convenience sampling. Multiple linear regression analysis was applied to analyze the data. The findings show that financial management practices and trustworthiness significantly affect the quality of financial reports, while human resource competence, internal control systems, information technology utilization, and stakeholder roles have no significant individual impact but collectively do. These results suggest that ethical stewardship and structured financial practices are key to improving report quality. Mosque administrators should prioritize training in financial management and technology adoption to enhance accountability. This study highlights the importance of trustworthiness and offers practical recommendations for improving financial transparency in Medan’s mosques.